RISK OF CARDIOVASCULAR DISEASE IN PATIENTS OF RHEUMATOID ARTHRITIS (RA) PRESENTING IN A TERTIARY CARE HOSPITAL OF PAKISTAN - Mushtaq, Muhammad Salman; Salim, Babur; Samreen, Saba; Nasim, Amjad; Gul, Haris (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess the cardio vascular disease (CVD) risk using framingham risk score and frequency of other co-morbidities associated with rheumatoid arthritis (RA). Study Design: Cross sectional descriptive study. Place and Duration of Study: Rheumatology department of Fauji foundation hospital (FFH), Rawalpindi. The duration of the study was six months, from Nov 2017 to Apr 2018. Material and Methods: RA Patients between 40 to 80 years of age were selected from rheumatology outpatient department (OPD) at Fauji Foundation Hospital (FFH) Rawalpindi. After 12 hours of fasting, venous blood was taken for total serum cholesterol (TC), triglycerides (TG), low density lipoproteins (LDL), high density lipoproteins (HDL) and ESR (mm/1st hour). Framingham risk score was calculated using online calculator and it was multiplied by a factor 1.5 as per European League against Rheumatism (EULAR) recommendations to find the correct cardiovascular risk. This gave us 10 year cardiovascular risk in each RA patient. Results: The study included 205 RA patients with a mean age (in years) of 53.12 ± 10.60. Mean duration of disease (years) was 9.71 ± 7.1. The commonest comorbidity in RA patients was hypertension found in 82 (40%) patients. 100 (48.78%) patients were overweight with mean body mass index (BMI) of 25.35 ± 4.96. Diabetes was found in 38 (18.5%) patients. 51 (24.87%) patients had high low density lipoprotein (LDL) with mean LDL of 116.75 ± 29.50 (mg/dL) whereas 88 (42.92%) patients had either borderline high or high total cholesterol with mean of 194.64 ± 30.62 (mg/dL). 104 (50.73%) patients had borderline high triglyceride levels with a mean of 166.48 ± 63.03 (mg/dL). 25 (12.2%) patients were smokers. 24(11.7%) patients had dexa scan proven osteoporosis ( T score <-2.5). Amongst all, 54 (26.3%) patients had low cardiovascular risk, 93 (45.4%) had moderate risk and 58 (28.3%) had high risk according to Framingham risk score. Conclusion: RA patients have high cardiovascular risk. Other co-morbidities like hypertension, high BMI, diabetes, dyslipidemia, smoking and osteoporosis add to the morbidity and mortality of these patients.